2020
DOI: 10.5713/ajas.19.0784
|View full text |Cite
|
Sign up to set email alerts
|

Effects of energy-protein supplementation frequency on performance of primiparous grazing beef cows during pre and postpartum

Abstract: Objective: Twenty-four pregnant Nellore primiparous grazing cows were used to evaluate the effects of energy-protein supplementation and supplementation frequency during pre (105 d before calving) and postpartum (105 d after calving) on performance and metabolic characteristics.Methods: Experimental treatments consisted of a control (no supplementation), daily supplementation (1.5 kg/d of concentrate/animal) and infrequent supplementation (4.5 kg of concentrate/animal every three days). During the pre and post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 34 publications
1
14
0
3
Order By: Relevance
“…For example, maternal protein supplementation during mid-gestation in cows tends to increase the pregnancy rate in the subsequent breeding season ( Rodrigues et al, 2021 ), while the supplementation during late gestation reduced maternal tissues mobilization ( Lopes et al, 2020 ), and may improve cows’ reproductive parameters. Although the costs of supplement are relatively high in a livestock production system, an alternative for decrease the feeding and labor costs may be achieved by reducing the frequency of energy-protein supplementation during prepartum, without causing negative effects in maternal performance and metabolism ( Moura et al, 2020 ).…”
Section: Fetal Programming and The Efficiency For The Deposition Of Muscle And Fatmentioning
confidence: 99%
“…For example, maternal protein supplementation during mid-gestation in cows tends to increase the pregnancy rate in the subsequent breeding season ( Rodrigues et al, 2021 ), while the supplementation during late gestation reduced maternal tissues mobilization ( Lopes et al, 2020 ), and may improve cows’ reproductive parameters. Although the costs of supplement are relatively high in a livestock production system, an alternative for decrease the feeding and labor costs may be achieved by reducing the frequency of energy-protein supplementation during prepartum, without causing negative effects in maternal performance and metabolism ( Moura et al, 2020 ).…”
Section: Fetal Programming and The Efficiency For The Deposition Of Muscle And Fatmentioning
confidence: 99%
“…On the other hand, many studies evaluating provision of different supplements on changes in the expression of some genes associated with gluconeogenesis (phosphoenolpyruvate carboxykinase [PEPCK]) and ureagenesis (carbamoyl phosphate synthetase-1 [CPS-1]) hepatic in cattle have been performed. Some authors have reported an increase in hepatic mRNA expression of PEPCK [ 4 ] and CPS-1 [ 5 ] when provided protein supplements, while others have not observed changes on hepatic mRNA expression of expression of PEPCK [ 4 ] and CPS-1 [ 6 ] when provided energy and protein supplements, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Primiparous cows appear to be more sensitive to nutrient intake and consequently, BCS changes more drastically comparing to mature cows (Moura et al, 2020;Spitzer et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…This relationship is especially critical for primiparous, due to the additional demands needed to continue their own growth combined with the stress of first lactation (Ciccioli et al, 2003). Thus, inadequate nutrient intake before and/or after calving has greater detrimental effects on reproductive performance in primiparous than mature cows (Moura et al, 2020;Sotelo et al, 2018;Summers et al, 2015). Supplementation programs for beef cows during prepartum and/or postpartum can be an alternative for improving the nutritional efficiency in grazing systems, especially when protein supplements are used (DelCurto et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation